(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1871)
Following on from his previous paper (see Vol VIII, pp.117-120), Mr Drummond continues his discussion of monumental slabs in the West Highlands. He comments on the ornamental features found on some of the stones on Iona, and then goes on to discuss some of the stone art found near the chapel of St Cormac at Eilean Mor.